2008
DOI: 10.1128/aem.00610-08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inhibitory Effects of Fluoride-Coated Tubes on Biofilm Formation by Using the In Vitro Dental Unit Waterline Biofilm Model

Abstract: This study aimed to establish an in vitro model to simulate biofilms formed in dental unit waterlines (DUWLs) and to investigate the ability of polyvinylidene fluoride (PVDF)-coated tubes to inhibit biofilm formation using this model. The water and biofilm samples were obtained from DUWLs which had been clinically used for 2.5 years, and the predominant bacteria were identified. A conventional polyurethane tube was incubated for 24 to 96 h in the mixed flora of isolated bacteria, and the optimal incubation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
13
1
4
Order By: Relevance
“…In our study, we found that Acinetobacter spp. made up less than 1% of the bacteria identified, counter to observations by Yabune et al (2008) and Barbeau et al (1996) that found a high proportion were this genus. Although bacterial diversity is likely to be different depending on the study, identification of Sphingomonas and Methylobacterium are common to each study and likely represent the core bacterial genera found in water from DUWLs.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In our study, we found that Acinetobacter spp. made up less than 1% of the bacteria identified, counter to observations by Yabune et al (2008) and Barbeau et al (1996) that found a high proportion were this genus. Although bacterial diversity is likely to be different depending on the study, identification of Sphingomonas and Methylobacterium are common to each study and likely represent the core bacterial genera found in water from DUWLs.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies performed in Canada using culturing techniques have confirmed that there can be significant contamination in water from DUWLs, and Sphingomonas paucimobilis, Acinetobacter calcoaceticus, Methylobacterium mesophilicum, and Pseudomonas aeruginosa were the predominant bacterial species (Barbeau et al, 1996) . Yabune et al (2008) have also shown that the dominant bacteria in water from DUWLs located in a Japanese dental hospital were also Sphingomonas paucimobilis, Acinetobacter haemolytics, and Methylobacterium mesophilicum. A more recent study using high-throughput DNA sequencing techniques has more comprehensively characterized the bacterial diversity of water from DUWLs in France (Costa et al, 2015) , showing frequent contamination by Sphingomonas and Halomonas.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present case, the main component of EU is 1,8-cineole and that of TTO is terpinene-4-ol but as already mentioned before, a host of other components namely citronellal, citronellol, citronellyl acetate, p-cymene, eucamalol, limonene, linalool, g-terpinene, a-terpinol, a-terpinene, terpinolene, r-cymene, and a-pinene are also present in varying amounts. 59 Thus in the case of EU and TTO films, the results obtained may indicate the cumulative effect of two factors: (a) bacterial adsorption on PVDF films promoted by OCP and HAp phase and (b) inhibitory effect of the essential oil coated film which serves to reinforce the antibacterial efficacy of the nanocomposite films. 17,19,[22][23][24] Since bacterial cells have a tendency to form biofilms on inorganic substrates, FESEM studies of the EU and TTO surfaces were also done to evaluate film-bacteria interfacial interactions (Fig.…”
Section: Antibacterial Assaymentioning
confidence: 96%
“…They also stress that it is necessary to develop and use effective methods of reducing DUWL microbiological load [8,38,39].…”
Section: Group N Share In Allergizing Group (%)mentioning
confidence: 99%